2020
DOI: 10.26565/2220-637x-2020-35-02
|View full text |Cite
|
Sign up to set email alerts
|

Design, rheology and microstructure of food-grade emulsion-based systems for delivery of vitamin D

Abstract: The fortification of food with vitamin D has several limitations because this group of fat-soluble compounds may degrade or undergo undesirable changes during technologic processing and storage of food. The purpose of this study was to investigate emulsions for vitamin D3 delivery in commercial foods. Oil-in-water (o/w) emulsions stabilized by mixture of various proteins (whey protein isolate (WPI), skimmed milk powder (SMP) and vegan protein isolate (VPI)) as emulsifiers and carboxymethylcellulose as thickeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(71 reference statements)
0
0
0
Order By: Relevance
“…The measurements were obtained at shear rates ranging from 0.01 to 300 s −1 and collected using Anton Paar RheoCompass 1.21 software (Anton Paar, Graz, Austria). The generalized flow of Casson's rheological model [8] was used to fit the viscosity curves as in [9,10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements were obtained at shear rates ranging from 0.01 to 300 s −1 and collected using Anton Paar RheoCompass 1.21 software (Anton Paar, Graz, Austria). The generalized flow of Casson's rheological model [8] was used to fit the viscosity curves as in [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…When processing the data, it was noted that the samples' viscosity was measured in a narrow range of shear rates from 0.1 to 5 s −1 due to the hardware limitations of the rotational viscometer used. In a previous study [10], it was shown that for some systems, the calculated parameters of the rheological model strongly depend on the interval of the shear rate range used in the calculation. The range of shear rates used is sufficiently adequate for calculating the τ c coefficient, but may overestimate the value of η c .…”
Section: The Assessing Of the Physical Stability Of The Emulsion-base...mentioning
confidence: 99%